Growth and Physiological Performance in Growth Phenotypes of the Carpet Shell Clam (Ruditapes decussatus) Fed Diets of Variable Lipid/Carbohydrate Ratios - Kristina Arranz; Iñaki Urrutxurtu; Dorotea Martínez-Patiño; Enrique Navarro (Aquaculture Nutrition)
Mixed suspensions of phytoplankton and yeast cells in different proportions were designed to achieve diets with a range of variation (0.6–2.2) in the ratio of lipid to carbohydrate while maintaining protein content constant. Juvenile specimens of the carpet shell clam (Ruditapes decussatus) from two segregated growth phenotypes (fast and slow growers) were food conditioned and the physiological components of the energy balance were determined with these different diet compositions in order to assess the combined effects of endogenous and nutritional factors on growth performance. Conditioning to lipid-rich diets increased growth rate relative to conditioning to carbohydrate-rich diets and resulted in higher scope for growth values in both growth groups. These dietary effects are mainly driven by differences in the absorption efficiency (AE) found between clams fed different food compositions, although the present results do not allow to ascertain whether the reduced AE recorded with the carbohydrate-rich diets results from reduced digestibility of yeasts cells due to structural restrictions or either reflects the digestive imbalance of lipids associated to higher production of metabolic fecal losses. Greater phenotypic plasticity was seen to enable the fast-growing clams fed a carbohydrate-rich diet to overcome the above digestive limitations through an overfeeding response; however, the resource to such kind of physiological mechanism appeared limited by the nutritional conditions (energetic status) prevailing during the conditioning phase.